SUPREALISM IN CONTEMPORARY IRAQI CERAMICS - Ammar Hussein fadel , Assist. Prof. Dr. Haider Raoufsaeed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Suprealism is a prominent sign in the modern Iraqi ceramics movement, especially in terms of the comprehensiveness that characterized the production of art in painting, sculpture and ceramics and combining them with a clear benefit from the opportunity that was afforded to him to communicate with international art, heritage and truth, and in particular through his porcelain, the realism he tried This research is an extrapolation and analysis of its foundations and elements, and the library’s lack of such research. As for the research procedures, in which the researcher specified his research community with (19) ceramic works from which the researcher intentionally chose his research samples that were identified with (3) ceramic works. Adopting the descriptive analytical method for their analysis, and concluded by analyzing the samples. Time established an urgent pressing role in its surreal themes, used the camera to record some situations and turn them into ceramic work, and a shift in its color uses between the frank, glowing truth, to a more accurate ceramic work, to the reality that bore the notions of inimitable expressionism and explicit colours. In addition, the researcher reached conclusions the characteristic of realistic reality by transferring the image with more accuracy and applying it realistically with measurements, color and reduction some things that happen spontaneously.